Leading Difficult Conversations Series #2: Preparing for the Conversation - Christy C. Chiarelli (EDIS)
This publication series is designed to equip leaders with strategies and tactics to use when they are tasked with having a difficult conversation. When approaching difficult conversations, leaders are encouraged to examine themselves prior to engaging in a hard conversation, because ultimately, a person can only change themself. In this series, the first topic to explore is preparing for the conversation. The components of proper preparation include clearly defining the issue and considering the motive behind the conversation. This new 3-page publication of the Department of Agricultural Education and Communication was written by Christy Chiarelli. https://edis.ifas.ufl.edu/wc378